EPOXY RESIN AND RELEASE AGENTS PART I: INFLUENCE OF EXTERNAL AND INTERNAL RELEASE AGENTS ON THE ADHESIVE PROPERTIES OF EPOXY RESIN - Bjekovic, Robert; Piotrowicz, Kinga (Journal of Applied Engineering Science, 2015)
A wide range of epoxy resins are molded to produce composite components for various applications. Release agents are generally used to facilitate the removal of the component from the mold. The work presented in this paper shows differences between release agents and resin during a RTM process. Adhesive properties of release agents in interaction with the resin are analyzed, with respect to pressure and temperature. It was found that the reaction of epoxy resin results in different breakaway forces from mould surfaces depending on used agents.
Keywords: RTM (Resin transfer molding) process; Internal and external release agent; Epoxy resin